Postfeminism and the fatale figure in neo-noir cinema - Lindop, Samantha (Palgrave Macmillan, 2020)
This book is a thought-provoking study that expands on film scholarship on noir and feminist scholarship on postfeminism, subjectivity, and representation to provide an inclusive, sophisticated, and up-to-date analysis of the femme fatale , fille fatale , and homme fatal from the classic era through to recent postmillennial neo-noir